Effective Cooling of Cassava Starch to Ethanol Bio-Reactors/Fermenters - Labadah, Edudzi Paul; Labadah, Joshua; Awere-Kyere, Lesley; Wheatley, Greg (International Journal of Chemical and Process Engineering Research, 2022)
This paper presents an effective way to control the temperature of bio-reactors (fermenters) used in ethanol production and to reduce the volume of cooling water required per square meter of ethanol produced. This paper specifically focuses on the fermentation of cassava starch using Saccharomyces cerevisiae at 32ºC. The flow across tube banks model is employed as the cooling mechanism of the bio-reactor. Cooling water at 28°C enters a shell containing five rows of fifteen (15) bio-reactors in a square in-line arrangement and exits the shell at 31.84°C. The total working volume of all fifteen (15) bio-reactors in the bank equals 180m^3. Each bio-reactor in the bank is designed to have an effective heat transfer area to volume ratio of two (2) to enhance heat transfer. The total quantity of cooling water required per cubic meter of ethanol produced is found to be 97.833m^3. A total amount of 1.303kW is required to power anchor impellers placed in each bio-reactor to provide mixing. The rotation speed of the impeller in each bio-reactor is 0.2〖rev·s〗^(-1). A total of 3.453*10^(-6) W is required to move cooling water through the bio-reactor bank at a speed of 3.942*10^(-5) ms^(-1). An overall heat transfer coefficient of 11.345W·m-2°C-1 was found for the bio-reactor cooling system. Employing flow across tube banks model in cooling ethanol bio-reactors required significantly less amount of cooling water per cubic meter of ethanol produced compared to using internal cooling coils.